Peningkatan Pengetahuan Ibu Tentang Iud Pasca Persalinan Setelah Diberikan Strategi Konseling Berimbang (SKB) Dengan Video Learning - Ake, Indo; Ramadany, Sri; Pelupessy, Nugraha; Ahmar, Hamdiah; -, Saleha (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This study aims to analyze the differences in pre and post treatment knowledge in thegroup of SKB Â without and SKB with Video Learning.Method: This type of research uses quasy experiments (pre-post test design). The study was conducted at the UPTD Puskesmas Pitumpanua Wajo Regency in November to December 2019. The sample in this study was 44 third trimester pregnant women each group (control group (LCS) and treatment (LCS with Video Learning) selected based on purposive sampling techniques. Counseling is carried out twice, namely in the antenatal period and 12 hours after delivery Data analysis with the Homogeneity of variance test and the Wilcoxon test.Results: Statistical test results showed that in the control group (p value: 0.001 <0.05) and intervention (pvalue: <0.001 <0.05) there were significant differences in knowledge before and after treatment. Increased knowledge in the intervention group was faster seen in the initial measurement to the first measurement while in the control group it was seen in the initial measurement to the second measurement.Conclusion: There are differences in pre and post treatment knowledge in the SKB and SKB groups with Video Learning. The counseling method uses SKB with faster video learning in increasing maternal knowledge about postpartum IUDs.Â